Shape and size constraints on dust optical properties from the Dome C ice core, Antarctica - Potenza, M. A. C; Albani, S.; Delmonte, B.; Villa, S.; Sanvito, T.; Paroli, B.; Pullia, A.; BACCOLO, GIOVANNI; Mahowald, N.; Maggi, V. (Scientific Reports, 2016)
Mineral dust aerosol (dust) is widely recognized as a fundamental component of the climate system and is closely coupled with glacial-interglacial climate oscillations of the Quaternary period. However, the direct impact of dust on the energy balance of the Earth system remains poorly quantified, mainly because of uncertainties in dust radiative properties, which vary greatly over space and time. Here we provide the first direct measurements of the aerosol optical thickness of dust particles windblown to central East Antarctica (Dome C) during the last glacial maximum (LGM) and the Holocene. By applying the Single Particle Extinction and Scattering (SPES) technique and imposing preferential orientation to particles, we derive information on shape from samples of a few thousands of particles. These results highlight that clear shape variations occurring within a few years are hidden to routine measurement techniques. With this novel measurement method the optical properties of airborne dust can be directly measured from ice core samples, and can be used as input into climate model simulations. Based on simulations with an Earth System Model we suggest an effect of particle non-sphericity on dust aerosol optical depth (AOD) of about 30% compared to spheres, and differences in the order of ∼10% when considering different combinations of particles shapes.